Patients with chronic three-vessel disease in a 15-year follow-up study: genetic and non-genetic predictors of survival - Máchal, Jan; Pávková-Goldbergová, Monika; Hlinomaz, Ota; Groch, Ladislav; Vašků, Anna (Medicine, 2014)
Genetic and non-genetic predictors of 15-year survival in patients with chronic three-vessel disease (3VD) were investigated. Coronary angiography was performed on 810 subjects with symptoms of stable ischemic heart disease in 1998. The patients with 3VD were genotyped for 23 candidate polymorphisms covering the PPAR-RXR pathway, matrix metalloproteinase-2, renin-angiotensin-aldosterone system, endothelin-1, cytokine genes, MTHFR and APO E variants. Fifteen-year survival data were obtained from the national insurance registry. All data were available in the case of 150 patients with 3VD. Statistical analysis used stepwise Cox regression with dominant, recessive, or additive mode of genetic expression. Involved variables included age, sex, BMI, blood pressure, diabetes, ejection fraction, left main stenosis, previously diagnosed coronary stenosis, myocardial infarction in personal history, and coronary bypass along with polymorphisms pre-selected by log-rank tests. Out of the 23 polymorphisms, four were included in the model construction. SNP in the IL-6 gene rs1800795 (-174 G/C) has been found to be a significant predictor of survival. This SNP was in a linkage disequilibrium with rs1800797 (-597 G/A) in the same gene (D'=1.0), which was also found to constitute a significant predictor of survival when rs1800795 was not included in the model construction. Age, increased BMI, diabetes, low EF, and left main stenosis were also significant predictors in all models. Age, increased BMI, diabetes, low ejection fraction, left main stenosis, and genetic variation in the IL-6 promoter were established as significant independent risk factors for the survival of patients with three-vessel disease.
Keywords: senioři; proporcionální rizikové modely; Genetic Predisposition to Disease; Proportional Hazards Models; interleukin-6; Retrospective Studies; DNA; Prognosis; Interleukin-6; nemoci koronárních tepen; Česká republika; polymerázová řetězová reakce; Polymerase Chain Reaction; Radiography; Middle Aged; registrace; mužské pohlaví; předpověď; Czech Republic; polymorfismus genetický; Registries; Follow-Up Studies; Coronary Artery Disease; následné studie; Polymorphism, Genetic; Forecasting; ženské pohlaví; prognóza; radiografie; retrospektivní studie; Humans; lidé středního věku; rizikové faktory; genetická predispozice k nemoci; Female; Aged; Risk Factors; lidé; Male